2008
DOI: 10.3748/wjg.14.2962
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for gastrointestinal neoplasms

Abstract: Endoscopic submucosal dissection (ESD) is an advanced technique of therapeutic endoscopy for superficial gastrointestinal neoplasms. Three steps characterize it: injecting fluid into the submucosa to elevate the lesion, cutting the surrounding mucosa of the lesion, and dissecting the submucosa beneath the lesion. The ESD technique has rapidly permeated in Japan for treatment of early gastric cancer, due to its excellent results of enbloc resection compared to endoscopic mucosal resection (EMR). Although there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(149 citation statements)
references
References 57 publications
5
134
0
10
Order By: Relevance
“…The identification of useful markers of GC risk is thus hoped for. Evaluating HPrelated chronic gastritis and determining which subjects are at high risk for developing GC is very important, and would likely increase the efficacy of GC screening by endoscopic or other examinations (Enomoto et al, 2010a;Mukoubayashi et al, 2007;Ohata et al, 2005), and strategic approaches to metachronous multiple GC after endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) performed as minimally invasive treatment for early GC (Gotoda, 2007;Kakushima & Fujishiro, 2008;Nakajima et al, 2006). In addition, in terms of GC prevention, it has become clear that HP-related chronic gastritis cannot be ignored as an origin of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of useful markers of GC risk is thus hoped for. Evaluating HPrelated chronic gastritis and determining which subjects are at high risk for developing GC is very important, and would likely increase the efficacy of GC screening by endoscopic or other examinations (Enomoto et al, 2010a;Mukoubayashi et al, 2007;Ohata et al, 2005), and strategic approaches to metachronous multiple GC after endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) performed as minimally invasive treatment for early GC (Gotoda, 2007;Kakushima & Fujishiro, 2008;Nakajima et al, 2006). In addition, in terms of GC prevention, it has become clear that HP-related chronic gastritis cannot be ignored as an origin of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, early gastric cancer is defined as adenocarcinoma confined to the mucosa or submucosa of the stomach and can be treated using endoscopic submucosal dissection (ESD), which is an advanced therapeutic technique that can offer extremely promising outcomes. 11,12 Examination of miRNA expression profiles has revealed that specific miRNAs are aberrantly expressed in various human cancers.…”
mentioning
confidence: 99%
“…The overall incidence of bleeding and perforation with ESD is 11% and 6% respectively [32][33][34]. Due to the widespread acceptance of gastric and oesophageal ESDs, the number of medical facilities that perform colorectal ESDs grew in recent years [35,36].…”
Section: Endoscopic Mucosal Resection (Emr)/endoscopic Submucosal Dismentioning
confidence: 99%
“…Patients with upper GI resection of tumoral lesions should be treated with intravenous PPI as for Forrest IIa ulcers [5]: High-dose PPI therapy improves healing rates and reduces the risk of delayed bleeding [33]. There are small successful series of over-the-scope-clips (OTSC) use in acute GI bleeding unresponsive to conventional methods, which is becoming a consistent approach [87].…”
Section: Haemorrhagementioning
confidence: 99%